2020
DOI: 10.1155/2020/6699515
|View full text |Cite
|
Sign up to set email alerts
|

Topology Optimization of Interactive Visual Communication Networks Based on the Non-Line-of-Sight Congestion Control Algorithm

Abstract: In this paper, an in-depth study of interactive visual communication of network topology through non-line-of-sight congestion control algorithms is conducted to address the real-time routing problem of adapting to dynamic topologies, and a delay-constrained stochastic routing algorithm is proposed to enable packets to reach GB within the delay threshold in the absence of end-to-end delay information while improving network throughput and reducing network resource consumption. The algorithm requires each sendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…After simulation experiments and analysis, it is confirmed that this method of designing the effect of the ocean landscape to coordinate and match, the quality of the design has been improved to a certain extent. The optimization of decorative patterns in color for ocean landscape design is the focus of literature [24], which uses the non-line-of-sight distance design theory and method. Literature [25] discussed the impact of the emergence of digital media on the design of network television interface style, with a professional and simple style, and suggested that it can be improved in the direction of personalization of the user.…”
Section: Introductionmentioning
confidence: 99%
“…After simulation experiments and analysis, it is confirmed that this method of designing the effect of the ocean landscape to coordinate and match, the quality of the design has been improved to a certain extent. The optimization of decorative patterns in color for ocean landscape design is the focus of literature [24], which uses the non-line-of-sight distance design theory and method. Literature [25] discussed the impact of the emergence of digital media on the design of network television interface style, with a professional and simple style, and suggested that it can be improved in the direction of personalization of the user.…”
Section: Introductionmentioning
confidence: 99%